HUMAN GENES CONTROLLING FEEDING BEHAVIOR OR BODY MASS AND THEIR FUNCTIONAL AND GENOMIC CHARACTERISTICS: A REVIEW - E. V. Ignatieva; D. A. Afonnikov; E. I. Rogaev; N. A. Kolchanov (Вавиловский журнал генетики и селекции, 2015)
The goals of this study were to create a compilation of genes controlling human body weight and feeding behavior and to summarize functional and genomic information on these genes. Information on 424 human genes was obtained from scientific publications, OMIM and meta-analysis of GWAS data. Four genes (BDNF, MC4R, PCSK1, and POMC) were confirmed by all three data sources; thus, these genes have the highest priority (No. 1). Genes of other two groups (3 and 29 genes) were confirmed by two of three data sources; thus having priority No. 2. Pathways important for body mass regulation were revealed, and they may be candidate pharmacological targets for obesity treatment. Regions of human chromosomes containing closely located genes from the compilation were revealed. Some groups of closely located genes included genes (ETV5, MIR148A, NFE2L3, and TMEM160) confirmed by GWAS meta-analysis only. This finding may be helpful in the identification of their functions. Use of Residual Variation Intolerance Score (RVIS) revealed genes with decreased tolerance to functional genetic variation: LRP1, LRP5, RAI1, FASN, LYST, RPTOR, DGKD, LRP1B, NCOA1, and ADCY3. The compilation can be used in genotyping for pathology risk estimation and for designing new pharmacological approaches for treatment of human obesity.